Mixed integer nonlinear programming tools: a practical overview - D’Ambrosio, Claudia; Lodi, Andrea (4OR, 2011)
We present a review of available tools for solving mixed integer nonlinear programming problems. Our aim is to give the reader a flavor of the difficulties one could face and to discuss the tools one could use to try to overcome such difficulties.